1975
DOI: 10.1159/000180522
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Hormone

Abstract: The factors that control sodium excretion have been the subject of considerable work in recent years. The natriuresis that follows expansion of the extracellular fluid volume is mediated to a large extent by inhibition of tubular sodium reabsorption. Of the several mechanisms proposed to explain this inhibition, considerable interest has followed the suggestion that a humoral substance is released into the blood stream in response to volume expansion. The present article reviews the evidence for and against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

1975
1975
1983
1983

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…We resorted to functional decapitation by a technique similar to that used by Cevese and Guyton (6) Studies by other investigators have implicated the brain as the source of the natriuretic factor. Klahr and Rodriguez (1) The absence of a significant natriuresis during acute blood volume expansion of intact dogs in the study of Cevese and Guyton (6) stands in sharp contrast to the marked natriuresis observed in our experiments and underscores several major differences between the experimental designs of the two studies. Cevese's and Guyton's experiments focused on the circulatory adjustments to an acute volume expansion stimulus administered as a pulse over 5 min.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…We resorted to functional decapitation by a technique similar to that used by Cevese and Guyton (6) Studies by other investigators have implicated the brain as the source of the natriuretic factor. Klahr and Rodriguez (1) The absence of a significant natriuresis during acute blood volume expansion of intact dogs in the study of Cevese and Guyton (6) stands in sharp contrast to the marked natriuresis observed in our experiments and underscores several major differences between the experimental designs of the two studies. Cevese's and Guyton's experiments focused on the circulatory adjustments to an acute volume expansion stimulus administered as a pulse over 5 min.…”
Section: Discussioncontrasting
confidence: 53%
“…Abstracts INTRODUCTION Expansion of the extracellular fluid volume elicits an increase in urinary sodium excretion. A large body of evidence implicates the participation of a humoral natriuretic factor in this response (1,2). Thus far, however, studies have failed to establish the identity and source of this factor, its mechanism of action, and its physiological role in the renal regulation of sodium balance.…”
mentioning
confidence: 99%
“…Finally, and most critically, the presence of the inhibitor in the urine of patients and dogs with chronic uremia and of the present dogs with normal renal function appears to correlate with the dictates of maintaining external sodium balance. A number of other investigators have now demonstrated the presence of natriuretic factor(s) or inhibitor(s) of sodium transport in the blood of animals and man using whole animal experiments (13)(14)(15)(16)(17)(18)(19)(20)(21) or in vitro assays (13,18,20,(22)(23)(24)(25)(26)(27)(28)(29). Similarly, extracts of urine have also been shown to contain natriuretic substance(s) (16,17,19,20,(30)(31)(32)(33)(34)(35)(36) or inhibitor(s) of sodium transport (20,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence implicates the participation of a humoral factor in this response (Klahr & Rodriguez, 1975). However, investigation has failed to establish the identity and source of the factor, its mechanism of action and its physiological role in the renal regulation of sodium excretion.…”
Section: Introductionmentioning
confidence: 99%